Risk Mitigation Design in the Production Process of Packaged Fruit Juice Drinks Using a Fuzzy Based House of Risk (HOR) Approach - Lufika, Raihan Dara; Sentia, Prima Denny; Ilyas; Erwan, Friesca; Andriansyah; Muthmainnah, Annisa (TALENTA Publisher, 2022)
Agro-industry is a sector that has quite diverse development potential, especially in the field of processing. One of them is processing fruit into fruit juice drinks. Nozy Juice is classified as an advanced MSME, but its competitive level is still lower than other agro-industry. This is because almost all of Nozy Juice's production activities are still done manually, giving rise to various risks that have an impact on decreasing the company's productivity level. To reduce this risk, a fuzzy-based House of Risk (HOR) approach is used which aims to identify the most critical risk agents. Then the risk mitigation design is carried out as an action plan. The essential risk of the 15 risk agents was a human error with an Aggregate Risk Potential (ARP) percentage of 24.275%. Furthermore, a risk mitigation design is carried out for 10 risk events. This is expected to minimize risks in the production process of packaged fruit juice drinks at Nozy Juice.